Assessing the Efficiency of Sharia Rural Banks: A Comparative Study Using DEA Frontier - Rahmanto, Dhidhin Noer Ady; Maulana, Hardiyansyah; Novi Febriyanti; M. Zidny Nafi’ Hasbi; Tyagita Dianingtyas Sudibyo (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2024)
The COVID-19 pandemic has negatively impacted various sectors, including health, the economy, and banking, leading to decreased purchasing power, weakened entrepreneurship, and threats to MSMEs. The Sharia Rural Banks (BPRS) complements other Sharia banks in Indonesia by meeting the community's financial needs in accordance with Sharia principles. Efficiency in banking serves as a key indicator to assess bank performance, determining whether a bank is operating effectively. Identifying the factors that influence efficiency in the banking sector is essential. This study employs a quantitative approach with a descriptive design, using secondary data from the BPRS annual financial reports for the first, second, third, and fourth quarters of 2023, obtained from the official OJK website. The research sample includes 20 BPRS in the Central Java and DIY Provinces, all registered with the OJK. The data was processed into input and output variables based on financial balance sheets and profit and loss statements. Analysis was conducted using the DEA Frontier Application with the Variable Return to Scale (VRS) model. Efficiency was measured on a scale from 0 to 1, where a score of 1 or 100% indicates full efficiency. This study, conducted online from May to July 2024, utilized annual financial report data sourced from the Financial Services Authority (OJK). The findings reveal that the average operational efficiency of BPRS in Central Java across the four quarters was 0.881, while in DIY, it was 0.940, indicating that BPRS in DIY demonstrated higher operational efficiency compared to those in Central Java.